The Phenomenon of the Hamza in Al-Taftazani (792 AH) in his Commentary on Al-Kashshaf - Abd, Suhaila Munshed; Zobaa, Bassem Rashid (Journal of Posthumanism, 2025)
The research aims to shed light on the venerable scholar Saad al-Din al-Taftazani, who is one of the scholars of the eighth century AH, who explored the depths of research in one of the most important interpretations that dealt with language and grammar after he saw that many distinguished scholars had turned to the study of Al-Kashaf, revealing the veils of its secrets, He entered their company to explore its secrets and subtleties, and to scatter to those who wish to learn more about it, so he wrote his footnote on Al-Kashaf, described his biography and scientific background, and showed the valuable scientific material that was organized in his footnote on the interpretation of Al-Kashaf. The research followed an analytical approach based on mentioning the author’s statement, then the commentator’s text on it, then stating his opinion on the guidance of the opinions of those who came before him and those who came after him, in addition to the opinions of modern scholars. The research reached a number of hoped-for results in this study, the most prominent of which can be summarized: Al-Taftazani dealt objectively and scientifically in his analysis of Al-Zamakhshari’s al-Hamz phenomenon, as he was not merely a mere transmitter of opinions or an imitator of previous grammarians but added much clarification and detail in the issues he addressed. Most of Al-Taftazani’s guidance on the al-Hamz phenomenon revolves around the Qur’anic readings, and he defended the Qur’anic readings and their readers, Al-Taftazani did not accept Zamakhshari’s challenge to the seven readings and the attribution of error to their reciters. He recognizes the recitations that are frequent, as well as the anomalous ones, as well as the narrations from them, which are cited by him and not by her. Al-Taftazani also relies on the languages of the Arabs to prove the validity of the reading, as in carrying the reading (I wanted to shield you with it) with hummz to one of the languages of the Arabs, which the research referred to in its places.